Steganography Image in Image using Modified method in Least Significant Bit (LSB) substitution (Baghdad Science Journal, 2007)
Steganography is the art of hiding and transmitting message through unsuspecting cover in an effort to conceal the existence of message. The aim of this paper is to design and implementation image in image steganography that hide the gray scale into color image, using embedding message in LSB of cover image. In Least Significant Bit (LSB) technique two methods ( Spin method and Look-up Table Method)have been suggested and compared with classical method. The imperceptibility of the stego image is assessed by using the mean square error (MSE) Root Mean Square Error (RMSE) (closeness measure), and peak signal-to-noise ratio (PSNR) measures used, the stego image, under different methods, have excellent quality (PSNR above 60 dB).